2019
DOI: 10.1029/2018jf004928
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Flow Above River Bedforms: Insights From Numerical Modeling of a Natural Dune Field (Río Paraná, Argentina)

Abstract: Bedforms are ubiquitous features in rivers and shallow seas, as mobile sediment is transported by flowing water. The mutual interaction of hydrodynamics and bedform has been widely studied in the laboratory over two‐dimensional bedforms having an angle‐of‐repose (30°) lee side and a relatively simple shape. However, the influence of bedform natural morphology and three‐dimensionality on the flow is still poorly constrained. The present work looks at how a natural three‐dimensional (3‐D) bedform field influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 49 publications
(168 reference statements)
0
28
0
Order By: Relevance
“…Johns and Xing, 1993; Omidyeganeh and Piomelli, 2013; Chen et al ., 2015). Of particular relevance to our study, Lefebvre (2019) used numerical modelling to show that the lateral orientation of the lee‐side slope relative to the mean direction of the flow passing over the bedform is a primary control of the lee‐side flow separation and turbulent wake production. Lefebvre (2019) found that as the lee‐side slope became less perpendicular to the mean flow direction, flow separation was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johns and Xing, 1993; Omidyeganeh and Piomelli, 2013; Chen et al ., 2015). Of particular relevance to our study, Lefebvre (2019) used numerical modelling to show that the lateral orientation of the lee‐side slope relative to the mean direction of the flow passing over the bedform is a primary control of the lee‐side flow separation and turbulent wake production. Lefebvre (2019) found that as the lee‐side slope became less perpendicular to the mean flow direction, flow separation was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance to our study, Lefebvre (2019) used numerical modelling to show that the lateral orientation of the lee‐side slope relative to the mean direction of the flow passing over the bedform is a primary control of the lee‐side flow separation and turbulent wake production. Lefebvre (2019) found that as the lee‐side slope became less perpendicular to the mean flow direction, flow separation was reduced. The exclusion of bedform three‐dimensionality in our model should be considered when extrapolating our results to natural rivers.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that dune shape has a major impact on energy decay. Recent simulations using 3D dune beds relate the presence and size of the flow separation zone and the wake, to the presence and properties of the slip face, as compared to the crest line or bedform height (Lefebvre, 2019). Approximations of the presence and size of reverse flow and wake can be derived from a bathymetric map (Lefebvre, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(2018) provided technical details of the free access software named Bedforms‐ATM (Bedforms Analysis Toolkit for Multiscale Modeling), which proposes standardizing the scale‐based discrimination and dimensionality quantification of natural bed forms in a single platform and whose structure encourages its expandability via collaboration from the community of users. The use of Bedforms‐ATM to conduct scientific research has been reported by Lefebvre (2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bradley and Venditti (2017) have compiled flow and dune dimension data for bed forms in unidirectional flows, and have made the data available as supplementary material; researchers have published nearly 400 000 datasets to date through the data publisher PANGAEA, including 125 related to bed forms; Gutierrez et al (2018) provided technical details of the free access software named Bedforms-ATM (Bedforms Analysis Toolkit for Multiscale Modeling), which proposes standardizing the scale-based discrimination and dimensionality quantification of natural bed forms in a single platform and whose structure encourages its expandability via collaboration from the community of users. The use of Bedforms-ATM to conduct scientific research has been reported by Lefebvre (2019).…”
Section: Introductionmentioning
confidence: 99%